2007
DOI: 10.1074/jbc.m703517200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Basis of Differential Cellular Responses of Phosphatidylinositol 3,4-Bisphosphate- and Phosphatidylinositol 3,4,5-Trisphosphate-binding Pleckstrin Homology Domains

Abstract: Phosphatidylinositol 3,4-bisphosphate (PtdIns(3,4)P 2 ) and phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P 3 ) are lipid second messengers that regulate various cellular processes by recruiting a wide range of downstream effector proteins to membranes. Several pleckstrin homology (PH) domains have been reported to interact with PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3 . To understand how these PH domains differentially respond to PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3 signals, we quantitatively determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 78 publications
8
152
0
Order By: Relevance
“…As summarized in Table 1, the protrudin-FYVE domain has high affinity for vesicles containing PtdIns(3,4)P 2 , PtdIns(4,5)P 2 , and PtdIns(3,4,5)P 3 , respectively. However, it shows very low affinity for vesicles containing PtdIns(3)P, PtdIns(4)P, or PtdIns(5)P. The K d values for binding of the protrudin-FYVE domain to vesicles containing PtdIns(3,4)P 2 , PtdIns(4,5)P 2 , and PtdIns(3,4,5)P 3 range from 100 to 200 nM, which are comparable with that for PtdIns(3,4,5)P 3 -specific PH domains determined under similar conditions (30). These values also compare well with the K d value for binding of other prototypical FYVE domains to vesicles containing PtdIns(3)P (49).…”
Section: Identification Of Pm-localized Lbds-supporting
confidence: 62%
“…As summarized in Table 1, the protrudin-FYVE domain has high affinity for vesicles containing PtdIns(3,4)P 2 , PtdIns(4,5)P 2 , and PtdIns(3,4,5)P 3 , respectively. However, it shows very low affinity for vesicles containing PtdIns(3)P, PtdIns(4)P, or PtdIns(5)P. The K d values for binding of the protrudin-FYVE domain to vesicles containing PtdIns(3,4)P 2 , PtdIns(4,5)P 2 , and PtdIns(3,4,5)P 3 range from 100 to 200 nM, which are comparable with that for PtdIns(3,4,5)P 3 -specific PH domains determined under similar conditions (30). These values also compare well with the K d value for binding of other prototypical FYVE domains to vesicles containing PtdIns(3)P (49).…”
Section: Identification Of Pm-localized Lbds-supporting
confidence: 62%
“…The membrane binding of PH domains is initially driven by nonspecific electrostatic interactions, which is followed by specific PI binding to increase the membrane residence time. A recent report demonstrated some PH domains anchor to the membrane through aliphatic residues adjacent to the PI-binding site (38).…”
Section: Ph Domainsmentioning
confidence: 99%
“…Our previous studies on Fab1, YOTB, Vac1, and EEA1 domain (FYVE) (50), phox homology (PX) (51), ENTH (52), and pleckstrin homology (PH) domains (53) showed that PtdInsP binding triggers membrane penetration of the domains by inducing an electrostatic potential switch and/or local conformational changes. To see whether PtdIns(4,5)P 2 exerts a similar effect on membrane binding of the two N-BAR domains, we measured the interaction of the domains with lipid monolayers in the presence and absence of PtdIns(4,5)P 2 .…”
Section: Role Of Ptdins(45)p 2 In Membrane Binding Of N-bar Domains-mentioning
confidence: 99%